Predictors of adherence to COVID-19 preventive measures among COVID-19 vaccine recipients in Tiruchirapalli city, South India: a cross-sectional study - K. Josephine Priya; N. B. Swetha; Barath Prashanth Sivasubramanian; A. K. Samina Ruquaya (Discover Public Health)
Abstract Background Measures such as social distancing, hand washing, and masking were recommended by the World Health Organization and Ministry of Health and Family Welfare to break the chain of transmission of COVID-19 infections. Following vaccination, a false sense of security may lead to decreased adherence to COVID-19 preventive behaviours. Data on predictors of COVID-19 Appropriate Behaviour (CAB) are not sufficiently available for the Indian population. Hence, we aimed to assess the adherence levels of vaccine recipients to CAB and identify predictors and barriers to adherence. Methods A cross-sectional study was conducted among COVID-19 vaccine recipients at a tertiary care hospital in Tiruchirapalli, Tamil Nadu between January to June 2022. Using systematic random sampling, 455 study participants older than 18 years, who had received the COVID-19 vaccine were recruited to the study. Sociodemographic data, knowledge of COVID-19 adherence, and barriers to CAB were evaluated using a questionnaire. Descriptive analysis was conducted based on frequency, means, and percentage. Analytical analysis was conducted based on bivariate logistical analysis and multivariate logistic regression models considering the odds ratio. 95% for confidence intervals and 5% for significance were respected. Results Mean age of the study population was found to be 35.17 ± 16.49 years. More than three-quarters of participants were found to be good at following COVID-19-Appropriate Behaviors. Participants aged over 40 years were more likely to experience satisfactory adherence levels [AOR = 2.20, (1.36–3.56)] compared to young participants. Those with education above the school level (> 12th standard) were almost twice more likely to experience adequate adherence levels [AOR = 1.93, (1.15–3.23)] than those with less education. Interestingly, those who had previously been infected with COVID-19 showed higher odds of satisfactory adherence [AOR = 2.13, (1.18–3.83)]. Conclusion This study showed that individuals over 40 years of age, those with higher education, and those with history of previous COVID-19 infection showed better compliance. Using social media as a targeted intervention focusing on younger populations, coupled with simplified health communication strategies for those with lower educational levels, are recommended. Innovative approaches such as user-friendly mask designs and creative protective solutions can further enhance preventive behaviour adherence in the community.